Plasma Melatonin and Progesterone Profiles of Suffolk and Romney Marsh Ewes Implanted with Melatonin during Anoestrus Season at Lower Latitudes in Southern Hemisphere - Sasa, Aya; Rodrigues, Paula Almeida; Nonaka, Keico Okino; Balieiro, Julio César de Carvalho; Coelho, Lia Alencar (Acta Scientiae Veterinariae, 2016)
Background: The subcutaneous implants of melatonin are stimulatory and mimic the positive effects of short photoperiod on reproduction in small ruminants. This study investigated the daily plasma melatonin profiles in ewes treated with melatonin implants and kept under natural photoperiod in Southeastern Brazil. The plasma progesterone concentrations were also investigated before and after melatonin implantation. Materials, Methods & Results: Romney Marsh (n = 11) and Suffolk (n = 10) ewes, which had been isolated from rams for at least 2 months prior to the beginning of the trial, were randomly allocated in two groups based on melatonin implant treatment (with or without melatonin implant). For plasma melatonin concentration, 43 days after melatonin implantation and 3 days before the ram introduction blood samples were collected every 2 hours during 24 hours. For plasma progesterone concentrations, blood samples were collected every once to twice a week for 2 different periods: prior to melatonin implantation and 46 days after the melatonin implantation and at the same day of the introduction of rams. The hormonal concentrations were determined by the radioimmunoassay method (RIA). The data were analyzed according to MIXED procedure (SAS) as repeated measurements for random animal effects. The effect of melatonin treatment on plasma melatonin 24-h period varied according to the breed. At the dark-phase, there were no plasma melatonin differences (P > 0.05) between implanted and no-implanted (228.02 ± 58.39 vs. 169.59 ± 48.39) Romney Marsh ewes whereas for Suffolk ewes the plasma melatonin levels were higher in implanted (305.61 ± 68.39 pg/mL) than no-implanted (151.26 ± 38.35 pg/mL) ones. At the light-phase, melatonin treatment effects could be evidenced and these differences (P < 0.01) consisted of higher melatonin values for implanted ewes and basal values for no-implanted ones in both breed groups. Before the melatonin implantation, the plasma progesterone levels were ˂ 1 ng/mL for Romney Marsh (0.41 ± 0.02 ng/mL) and Suffolk (0.47 ± 0.02 ng/mL) ewes. During the ram introduction period, no melatonin treatment effect was observed on plasma progesterone concentrations in both breed groups, but 2 days after ram introduction the plasma progesterone concentrations increased the mean values > than 1 ng/mL in implanted and no-implanted Suffolk ewes. In implanted Romney Marsh ewes the elevation of progesterone mean values was weak whereas in no-implanted Romney Marsh ewes the progesterone levels were maintained ˂ 1 ng/mL during all the blood sample collection times. Discussion: The melatonin treatment also produced a similar model of daily melatonin levels as reported previously by others, which is characterized by high plasma melatonin concentrations during the light phase of the day. The effect of melatonin implants on plasma melatonin profiles interacted with breed confirming an individual response to melatonin implantation which is proportional to genetic individual variation pattern of melatonin secretion. Before the melatonin implantation all Romney Marsh and Suffolk ewes were judged to be in non-ovulatory period (anoestrus) with plasma progesterone mean values lower than 1 ng/mL. The melatonin treatment helped to induce the ovulatory activity in most of the ewes that were in anestrous at the time of melatonin implantation and the efficacy of this treatment depends on the individual variation in ovulatory response to ram introduction. In Southeastern Brazil., melatonin implant altered the daily plasma melatonin profiles of Suffolk and Romney Marsh ewes by increasing the melatonin levels during the light-phase of the day. Melatonin implant also induced an ovulatory response in Suffolk and Romney Marsh after the introduction of the rams. For no-implanted Suffolk ewes, the male effect is sufficient to provoke an ovulatory response.